Temporal Variation of Soil Physical Quality under Conventional and No-Till Systems - Soracco, Carlos Germán; Lozano, Luis Alberto; Villarreal, Rafael; Melani, Esteban; Sarli, Guillermo Oliverio (2018)
Determination of soil physical quality (SPQ) is very important because it is related to many important soil processes. However, it is not clear which indicators should be considered in this evaluation, and information about temporal variation of SPQ under different soil tillage systems is scarce. The aim of this study was to determine the effects of no tillage (NT) and conventional tillage (CT) on temporal variation of capacity SPQ indicators [bulk density (BD), macroporosity (Pmac), air capacity (AC), plant available water capacity (PAWC), relative field capacity (RFC), Dexter's (S), and structural stability index (SSI)], and dynamic SPQ indicators [field saturated hydraulic conductivity (K0), water-conducting macroporosity (εma), and mesoporosity (εme); and pore continuity indexes based on water flux of total porosity (CWTP), of macroporosity (CWmac), and of mesoporosity (Cwmes)]. Additionally, the effect of the soil management system on corn yield was evaluated. Measurements and determinations were made at four different moments/cropping stages in the corn growing season (BS: before seeding; V6: six leaf stage; R5: physiological maturity; and AH: after harvest). Capacity SPQ indicators were derived from the soil water retention curve determined using sand box and pressure chambers, and dynamic SPQ indicators were derived from field infiltration data measured using a tension disc infiltrometer. Most capacity SPQ indicators were affected by the moment/cropping stage in which samples were taken, but followed similar trends and had similar values under both treatments, particularly in the AH stage. Dynamic SPQ indicators varied differently during the growing season depending on the management system. Under NT, most dynamic indicators increase from BS to V6 and decrease again at AH, whereas under CT, they follow a different trend, decreasing from BS to V6, remaining constant until R5, and increasing at AH. Corn yield was lower under CT (NT: 10,939 kg ha−1; CT: 8,265 kg ha−1). These results emphasize the need to include dynamic SPQ indicators, and their temporal variation when evaluating cropping systems with the aim of modeling crop yields. The capacity SPQ indicators were not able to distinguish between treatments.